Fairness in Access to Higher Education in a Global Perspective Reconciling Excellence, Efficiency, and Justice - Meyer, Heinz-Dieter.; John, Edward P. St.; Chankseliani, Maia.; Uribe, Lina.; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2013)
The purpose of this volume is to help jump-start an urgently needed conversation about fairness and justice in access to higher education to counteract the ubiquitous mantras of neoliberal globalization and managerialism. The book seeks to carve out a strong moral and normative basis for opposing mainstream developments that engender increasing inequality and market-dependency in higher education. The book$1 (Bs chapters consider how different national communities channel access to higher education, what their (3z(Bimplicit social contracts(3y (Bare, and what outcomes are produced by different policies and methods. The book is essential reading for scholars of higher education and students concerned with increasing inequality in a globalizing educational marketplace.s
Keywords: Education; Education; Education (general).